-5y+4=-6y+5

Simple and best practice solution for -5y+4=-6y+5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5y+4=-6y+5 equation:


Simplifying
-5y + 4 = -6y + 5

Reorder the terms:
4 + -5y = -6y + 5

Reorder the terms:
4 + -5y = 5 + -6y

Solving
4 + -5y = 5 + -6y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '6y' to each side of the equation.
4 + -5y + 6y = 5 + -6y + 6y

Combine like terms: -5y + 6y = 1y
4 + 1y = 5 + -6y + 6y

Combine like terms: -6y + 6y = 0
4 + 1y = 5 + 0
4 + 1y = 5

Add '-4' to each side of the equation.
4 + -4 + 1y = 5 + -4

Combine like terms: 4 + -4 = 0
0 + 1y = 5 + -4
1y = 5 + -4

Combine like terms: 5 + -4 = 1
1y = 1

Divide each side by '1'.
y = 1

Simplifying
y = 1

See similar equations:

| 3x^2-14x=-18 | | 12x+6-3=11x-3 | | -10+3+6=-10 | | -4v^2-13v-3=0 | | -(8y+3)-(-7-4)=-1 | | 0.30(18)+0.05x=0.15(18+x) | | 8-4x+-6x=50 | | 4(2x-1)=2(3x+8) | | 4(3x+12)=2(2x+4) | | 1000=x+(x*.8) | | 3=2e^4x | | 9(x-36)=18 | | 2(x+4)=6(2x+3) | | 7(4x+6)+15= | | 4x-5=11-89 | | 6x+35=15x-55 | | 5a-3-4a+3=8 | | (4x^2+3x+5)-(6x^2-8)= | | 6a-2-5a+2=-2 | | X^2+17x=-72 | | -4a+3a-6=-4 | | 9x-19=5x+12 | | 6q-9=4q-19 | | c-5*4=-48 | | 4x+5=24 | | 6x-4=3x+2 | | 142-5x=40x+22 | | 5y-13=3y+1 | | 1+3=x | | 12-10x=46-24x | | 12x^3-6x^2-24x+18=0 | | 145=5v |

Equations solver categories